An Efficient Ultrasound Promoted One-Pot Three-Component Synthesis and Antibacterial Activities of Novel Pyrimido[4,5-b]quinoline- 4,6(3H,5H,7H,10H)-dione Derivatives - S. Jourshari, Maryam; Mamaghani, Manouchehr; Tabatabaeian, Khalil; Shirini, Farhad; Rassa, Mehdi; Langhari, Hadiss (Letters in Organic Chemistry, 2012)
A series of novel pyrimido[4,5-b]quinoline-4,6(3H,5H,7H,10H)-dione derivatives was synthesized by one-pot three-component reaction of the appropriate aldehyde, dimedone or cyclohexanedione and 6-aminothiouracil in ethanol under ultrasonic irradiation at 50 oC in short reaction times (1.5-3 min) and excellent yields (94-99%). The antibacterial activities of the synthesized compounds were evaluated on M. leuteus, B. subtilis, E. coli and Ps. aeruginosa. All the synthesized products showed good antibacterial activities.
Keywords: 6-aminothiouracil